1980
DOI: 10.3109/01485018008986982
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subtoxic Levels of Lead and Cadmium on Urogenital Organs of Male Rats

Abstract: Higher incidence of prostate cancer among lead and cadmium smelter workers has been reported. Forty male rats were divided into four groups. Group I served as control; Group II was injected intraperitoneally, close to the site of the prostate, with 0.05 mg lead acetate; Group III was injected with 0.05 mg cadmium chloride; and Group IV was injected with a combination of 0.025 mg lead and 0.025 mg cadmium chloride. After daily injection for one month, lead and cadmium had a synergistic effect on testicular dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In a short-term rodent study, Fahim and Khare (1980) detected squamous metaplasia of the prostatic epithelium in rats repeatedly injected with cadmium and lead over 10 wk. This suggested to the authors that progressive precancerous changes had occurred with this combined treatment.…”
Section: Related Studies In Rodentsmentioning
confidence: 98%
“…In a short-term rodent study, Fahim and Khare (1980) detected squamous metaplasia of the prostatic epithelium in rats repeatedly injected with cadmium and lead over 10 wk. This suggested to the authors that progressive precancerous changes had occurred with this combined treatment.…”
Section: Related Studies In Rodentsmentioning
confidence: 98%
“…In animal studies, lead and alcohol synergistically inhibited blood ALADH activity and hepatic aspartate aminotransferase/glutamate oxaloacetate transaminase 1 (AST/GOT) and alanine aminotransferase/glutamate pyruvate transaminase 1 (ALT/GPT) activity, depressed dopamine and 5-hydroxytryptamine levels in rat brain, increased the lead burden in tissues and organs, and elevated blood zinc protoporphyrin (Dhawan et al, 1989;Flora and Tandon, 1987). Smokers are also at an elevated risk of lead intoxication because cigarette smoke contains lead and other heavy metals such as cadmium and mercury (Calabrese, 1978) that have been shown to be synergistic in experimental animals (Congiu et al, 1979;Exon et al, 1979;Fahim and Khare, 1980). Alcohol influences the metabolism of mercury after exposure to mercury vapor.…”
Section: Alcohol and Tobaccomentioning
confidence: 95%
“…The effect of age on concentrations of metals in blood has been previously demonstrated (for example, Lock and others, 1992;Burger and others, 2018); however, sample size may also have affected age comparisons. exposure to lead and cadmium caused "greater than additive" or synergistic lead toxicity (Der and others, 1976;Fahim and Khare, 1980;Marlowe and others, 1985;Lockett and Leary, 1986;Saxena and others, 1989), whereas nine studies concluded that lead and cadmium toxicities were simply additive (Thawley and others, 1977;Fowler and Mahaffey, 1978;Perry and Erlanger, 1978;Roels and others, 1978;Kopp and others, 1980a, b;Buchet and others, 1981;Mahaffey and others, 1981;Voors and others, 1982). Cobbina and others (2015) also found synergistic effects among lead, cadmium, or copper in rat tissues during low-dose chronic exposures.…”
Section: Bloodmentioning
confidence: 99%